Intelligent Monitoring and Predictive Analytics for Cloud-Native Applications using Machine Learning - Pende, Kishan K.; Choudhari , P. M. (International Journal on Advanced Computer Engineering and Communication Technology, 2025)
Cloud-native applications have become essential components of today’s digital infrastructure due to their flexibility, scalability, and efficiency. However, their highly distributed and dynamic environments create complex monitoring challenges that conventional reactive systems fail to address effectively. Such reactive systems identify problems only after they occur, causing downtime, performance degradation, and revenue loss. To overcome these issues, this paper presents an AI-driven proactive monitoring framework that combines automation and predictive analytics. The framework integrates Prometheus for collecting detailed performance metrics and Grafana for real-time visualization, while a predictive engine powered by Isolation Forest and LSTM models anticipates anomalies and system failures before they occur. On average, the system predicts potential disruptions 10–15 seconds before a critical threshold is reached. In addition, automated workflows built with n8n and Jenkins execute corrective actions such as service scaling and restarts, enabling a self-healing environment. This intelligent and proactive system significantly improves reliability, reduces downtime, and transitions cloud monitoring from reactive problem-solving to predictive maintenance.